Least developed countries in the WTO dispute settlement system - Tania, Sharmin (Springer, 2013)
Existing literature on the developing countries' experience with the WTO dispute settlement system (DSS) has paid scant attention to the participation issue of the least developed countries (LDCs), which currently form one-fifth of the WTO membership but constitute less than one per cent of participation in DSS. This article fills this gap by examining several dimensions of LDCs' participation. Upholding the significance of LDCs' participation it explores the challenges faced by LDCs at the pre-litigation, litigation and implementation stage emanating from power asymmetries, resource constraints and flawed DSS remedies. The article particularly looks into the nature of LDCs' participation, which is mostly in the category of third parties. In doing so, it evaluates the third-party participation of Benin and Chad in US - Upland Cotton to ascertain whether third-party participation could be an alternative for LDCs to participate as co-complainants. It analyzes the special and differential treatment provisions of the DSU to further scrutinize whether these provisions and the way they are interpreted and applied in the WTO Panel Reports and the Appellate Body Reports are facilitative for LDCs' participation. Finally, the article makes recommendations to address the challenges on the part of LDCs and to reform DSS so as to make it effective for LDCs' participation.